2002
DOI: 10.1038/sj.onc.1205257
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of B-type cyclins alters chromosomal segregation

Abstract: To identify genes which overexpression results into chromosomal instability (CIN), we developed a biological approach based on a yeast indicator strain in which CIN can be detected by a sectoring phenotype. Screening in this strain of a yeast genomic library cloned into a high copy vector led us to identify, among the clones generating 100% of sectoring colonies, Clb5, one of the six B-type cyclins present in yeast. Overexpression of cyclin B2 and cyclin B1, the two human homologs of Clb5, in the CIN indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 33 publications
2
66
0
Order By: Relevance
“…63 In contrast, cells with the CHH founder RMRP mutation had significantly increased levels of cyclin B2 mRNA. 63 Cyclin B2 is known to contribute to chromosomal instability through alterations of the mitotic spindle checkpoint, 64 which suggests another possible explanation for the bone marrow dysfunction seen in CHH. Recent work by Maida et al has revealed a connection between RMRP and TERT.…”
Section: Cartilage Hair Hypoplasiamentioning
confidence: 99%
“…63 In contrast, cells with the CHH founder RMRP mutation had significantly increased levels of cyclin B2 mRNA. 63 Cyclin B2 is known to contribute to chromosomal instability through alterations of the mitotic spindle checkpoint, 64 which suggests another possible explanation for the bone marrow dysfunction seen in CHH. Recent work by Maida et al has revealed a connection between RMRP and TERT.…”
Section: Cartilage Hair Hypoplasiamentioning
confidence: 99%
“…39 Subsequent publications have confirmed the association between cyclin B1 and chromosomal instability both in yeast and in mammalian cells transformed by the Pim-1 oncoprotein. 40,41 Interestingly c-Myc and Pim-1 are well-described cooperating oncoproteins 42 for murine lymphomagenesis, although neither cyclin B1 levels in these tumors nor their levels of CIN have been reported. It is intriguing that cryptic S-phase-promoting activity has been attributed to cyclin B1/cdk1 when it is redirected from its usual sequestered location in the cytoplasm to the nucleus.…”
Section: Mechanistic Underpinnings Of C-myc Mediated Gimentioning
confidence: 99%
“…This paradox may be explained by the fact that securin is required to fully activate separase and, therefore, loss of securin as well as undegradable securin leads to inactive separase with problems in sister chromatid separation and loss of chromosomes. Also, high B cyclin levels result in genomic instability (Sarafan-Vasseur et al, 2002;Wa¨sch and Cross, 2002) and can be found in colon (SarafanVasseur et al, 2002;Wang et al, 2003) or lung cancer (Soria et al, 2000). Deregulation of APC-dependent proteolysis of these substrates is thereby important and very likely to be involved in tumorigenesis.…”
Section: Deregulated Proteolysis In Cancermentioning
confidence: 99%
“…Deregulation of cyclins and other cell cycle regulators can cause aberrant proliferation and genomic instability (Spruck et al, 1999;Lengronne and Schwob, 2002;Sarafan-Vasseur et al, 2002;Wa¨sch and Cross, 2002). Aberrant expression of different cyclins can be detected in various malignant tumors Chetty, 1998, 1999;Yam et al, 2002), with important implications for clinical oncology.…”
Section: Deregulated Proteolysis In Cancermentioning
confidence: 99%